The Post-Communist World – Crisis or Evolution? (Five Years behind us...) (Czech Journal of International Relations, 1994)
The results of elections in various post-communist countries in the past year raise certain doubts about the direction of their development. Starting with Russia, through Poland, Hungary, Ukraine and ending with this year's elections in Slovakia, the socialists are returning to power. Losses liberals and conservatives seemed to signal at least a slowing down of the pace of change, if not a direct change in the direction of development. The rise of ultra-nationalism in Russia, the crisis of Ukraine's integrity, harsh anti-Hungarian rhetoric in Bratislava and especially the ongoing ethnic war in Bosnia keep the development of the post-communist part of Europe at the forefront of the European security agenda as a real or potential source of instability and conflict.The fifth anniversary of the fall of the Berlin Wall provides a good opportunity for a retrospective look and reflection on the direction of today's development. Is the post-communist world in a crisis of disorientation, or is it continuing to evolve towards democracy and prosperity?